A responsabilidade patrimonial na execução e o direito fundamental do acesso ao judiciário - Bastos, Bianca (2021)
The notion of access to justice guides de modern vision of labor execution, materialized in the execution of the sanction on a given patrimony, which may belong to a debtor or a third part. The definition of the parties in the execution, as well as the assets that are subject to state power for the realization of the credit guarantee, is made based on the obligations arising from the relations of material law and, in this case, of Labor Law.In addition to the contracting party, there are legal institutes that define labor liability for other subjects, such as the economic group, the labor succession, disregard doctrine and outsourcing. The application of these institutes in the executive process presupposes the making of assertions about their current functioning in Labor Law, which will compose the general framework of a more advanced proposal, capable of distinguishing them from the patrimonial responsibility of the Civil Procedure Code. At this point, the study will determine which are the compatible situations of the common procedural law with the labor enforcement. In a scenario in which the mandatory labor law institutes do not have complete correspondence with the assumptions of common law, this paper intends to designate a space in the methodology of the procedural liability system, pointing out the impacts and solutions, and also classifying the labor officer as a debtor or a third part, according to the criterion of the primary or secondary property liability. The impact of this proposal is to establish a procedural responsibility in the field of labor enforcement also in relation to mandatory institutes specific to Labor Law. As a final result, it will broaden the understanding of the State´s sanctioning action for the realization of labor credit, as a way of accessing the Judiciary department, and with respect to the principles of due process of law